2017
DOI: 10.5897/ajb2017.15899
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak investigation of Newcastle disease virus from vaccinated chickens in Eritrea

Abstract: Newcastle disease (ND) is one of the most important infectious viral diseases of poultry in Eritrea.Diagnosis of ND virus infection in Eritrea has been mainly based on clinical examination and post mortem lesions. This study describes ND diagnosis using reverse transcription polymerase chain reaction PCR (RT-PCR), virus isolation and serological techniques (haemaglutination inhibition test) from two times vaccinated 40 days old chicks in Keren poultry farm. Generally clinical signs and postmortem lesions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
2
1
Order By: Relevance
“…The current study reported that NDV has distinctive clinical signs such as respiratory difficulties, depression, head twisting, and greenish-white diarrhea. This is consistent with the results of previous studies by Alexander [24], Bereket et al [25], and Khorajiya et al [26]. A previous study by Wise et al [27] reported that NDV-infected chickens also showed enlargement and inflammation of the eyes, diarrhea, and lack of appetite.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study reported that NDV has distinctive clinical signs such as respiratory difficulties, depression, head twisting, and greenish-white diarrhea. This is consistent with the results of previous studies by Alexander [24], Bereket et al [25], and Khorajiya et al [26]. A previous study by Wise et al [27] reported that NDV-infected chickens also showed enlargement and inflammation of the eyes, diarrhea, and lack of appetite.…”
Section: Discussionsupporting
confidence: 92%
“…At necropsy, the mucus in the respiratory tract and pin-point hemorrhages in the proventriculus were observed in the suspected chickens. These results strongly agree with those of other studies [25,28]. Based on the clinical signs and the postmortem findings, the chickens obtained in the study were considered to be infected with NDV.…”
Section: Discussionsupporting
confidence: 91%
“…These results were in line with some other reports. 21 , 24–26 Hemorrhagic laryngotracheitis, congestion and edema of the lungs have been reported 27 ; the reported lesion is different from the present study, and this variation may be due to different strains of NDV that can affect different organs of the chickens. In this study, the observed lesions were indicative of ND depending on the observed gross pathological lesions.…”
Section: Discussioncontrasting
confidence: 74%
“…The overall morbidity, mortality and case fatality rates observed in infected chickens in the study area were 18.7%, 9.5% and 50.5%, respectively. According to one study 21 , 21.21% mortality was reported from chickens exposed to outbreaks of ND. Similarly, Saidu and Abdu 23 reported a 97.7% mortality rate which is higher than the present finding.…”
Section: Discussionmentioning
confidence: 99%
“…Also see Pateman (1990, p. 47) and Greenfield (1980, p. 24). Taking this one step further, Bereket (1980b, pp. 34–35) contended that Eritrean nationalism is hardly a new phenomenon.…”
mentioning
confidence: 99%